2013
DOI: 10.1016/j.bbrc.2013.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase is phosphorylated in response to insulin stimulation in skeletal muscle

Abstract: Type 2 Diabetes (T2DM) is the seventh leading cause of death in the United States, and is quickly becoming a global pandemic. T2DM results from reduced insulin sensitivity coupled with a relative failure of insulin secretion. Reduced insulin sensitivity has been associated with reduced nitric oxide synthase (NOS) activity and impaired glucose uptake in T2DM skeletal muscle. Upon insulin stimulation, NO synthesis increases in normal adult skeletal muscle, whereas no such increase is observed in T2DM adults. End… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 25 publications
(28 reference statements)
0
25
0
1
Order By: Relevance
“…Increases in RyR1-associated nNOSl activity may also contribute to RyR1 hypernitrosylation (21,39,67). To test the possibility that nNOSl was also driving RyR1 hypernitrosylation, we determined nNOSl protein expression and the fraction of active serine 1446 phosphorylated nNOSl (35,52). nNOSl expression and the fraction of ser 1446 phosphorylated nNOSl were unaffected in GSNOR -/-muscles, suggesting that nNOSl was not driving RyR1 hypernitrosylation ( Fig.…”
Section: Fig 3 Gsnor Negatively Regulates Ryr1mentioning
confidence: 99%
“…Increases in RyR1-associated nNOSl activity may also contribute to RyR1 hypernitrosylation (21,39,67). To test the possibility that nNOSl was also driving RyR1 hypernitrosylation, we determined nNOSl protein expression and the fraction of active serine 1446 phosphorylated nNOSl (35,52). nNOSl expression and the fraction of ser 1446 phosphorylated nNOSl were unaffected in GSNOR -/-muscles, suggesting that nNOSl was not driving RyR1 hypernitrosylation ( Fig.…”
Section: Fig 3 Gsnor Negatively Regulates Ryr1mentioning
confidence: 99%
“…It has been reported that exercise induces the phosphorylation of nNOSμ at S1446 in skeletal muscle via AMP-activated protein kinase (AMPK), which is itself activated by exercise [43, 44]. Our previous work demonstrated that insulin signaling in myotubes and H 2 O 2 treatment of cardiomyocytes also leads to phosphorylation of nNOSμ S1446 and a concomitant increase in NO production (Figure 1; [28, 38]), so a similar mechanism was considered. As shown in Figure 6A, B, treatment with 400 µM H 2 O 2 resulted in a 2.3-fold increase in nNOSμ S1446 phosphorylation.…”
Section: Resultsmentioning
confidence: 98%
“…Previous results from our laboratory demonstrated that nNOSμ was phosphorylated at S1446 in C2C12 myotubes and in mouse skeletal muscle via the insulin-signaling cascade, resulting in increased NO synthesis [38]. A likely candidate for catalysis of this phosphorylation is the insulin-activated protein kinase B (Akt), more specifically, the Akt2 isoform.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is not possible to specifically measure nNOS activity alone in vivo, we evaluated the fraction of active serine1446 phosphorylated nNOSl, the primary enzymatic NO source in muscle (34,61). Loss of GC1 decreased the fraction of active serine1446 phosphorylated nNOSl by 40% ( Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%